IMPACT OF SANCTIONS ON INTERNATIONAL PRIVATE LAW RELATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the economic implications of sanctions and their influence on international private law connections. The rising prevalence of unilateral sanctions in the contemporary era, as a facet of public law in global relations, necessitates a thorough investigation into their repercussions on relationships involving individuals and legal entities with foreign elements. The paper delves into the complexities of categorizing sanctions and their effects on the negotiation and fulfillment of cross-border agreements. Furthermore, it explores emerging trends, such as the redomiciliation of legal entities to sustain operations in more advantageous conditions. Drawing from thestudy, a set of preventive measures is suggested to mitigate the impact of sanctions on the execution and progression of international private law relations.